Early-Life Stress and Psychiatric Disorders: Epidemiology, Neurobiology and Innovative Pharmacological Targets - Ventriglio, A.; Gentile, A.; Baldessarini, R.J.; Bellomo, A. (Current Pharmaceutical Design, 2015)
The modern concept of stress is based on responses to events or factors (“stressors”) experienced as aversive, threatening or excessive for maintaining physiological equilibrium of an organism. Prolonged exposure to stressors, particularly during early life, is strongly associated with later psychiatric disorders. Underlying mechanistic connections between stress responses and development of psychiatric illnesses remain uncertain and typically appear to be nonspecific. Relevant candidate mechanisms are likely to include the hypothalamic-pituitary-adrenal (HPA) axis, marked by sustained excessive release of cortisol from the adrenal cortex. In turn, this process is influenced by and alters various central neurotransmitter and other molecular signaling systems that include glutamate, dopamine, serotonin, and neurotrophic peptides. A dditional manifestations of stress include altered neurogenesis and neuroplasticity, as well as oxidative neuron-damaging effects. The complex molecular systems involved in these processes present many opportunities for innovative pharmacological interventions that may have preventive or therapeutic benefits regarding mental illnesses arising from stress.
Keywords: neurogenesis